USING â€œAVATAR: THE LEGEND OF KORRAâ€ ANIMATED MOVIE-BASED PROJECT TO IMPROVE LISTENING COMPREHENSION - Solehah, Solehah; Ikhsanudin, Ikhsanudin; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractAs a pre-experiment, this study concentrates on measuring the effectiveness of â€œAvatar: The Legend of Korraâ€ animated movie-based project to improve listening comprehension. The sample of this research is a group of eighth grade students of SMP Muhammadiyah 2 in School Year 2015/2016. Pretest and posttest are the instruments of the data collection. This research has fulfilled its purpose, that is to study the effectiveness of â€œAvatar: The Legend of Korraâ€ animated movie-based project to improve listening comprehension of eighth grade students. It is proven that the effectiveness is strong by 1.41 of effect size, which means the fourth hypothesis is accepted. Treatment was given once for two-week long, including monitoring, project progress, and assessment (posttest). A 25% increase in score is found between pre-test (49.27) and post-test (65.37). This proved the â€œAvatar: The Legend of Korraâ€ animated movie based project improved the studentsâ€™ listening comprehension. Â Keywords: Animated Movie, Based Project, Listening